Teaching Analogies Strategy on Students’ Achievement in Vocabulary - Linda Astuti Rangkuti (English Teaching and Linguistics Journal (ETLiJ), 2021)
The objective of this research was to investigate if analogies strategy significantly affected students’ achievement in vocabulary. The research was conducted by using experimental research design that involved two groups, namely experimental group and control group. The population was all the students of grade VIII of SMP Al–Washliyah 9 Medan with total number of the population was 90 students. There were three classes, namely VIII A, VIII B, and VIII C. each class consisted of 30 students. The sample was carried out in class VIII A and VIII B by proposive sampling technique. Thus the sample was 60 students. The experimental group was taught by applying analogies strategy whereas the control group was taught conventionally. The instrument for collecting the data was a multiple choice test. The obtained data were analyzed by using t-test formula. Data analysis resulted that value was higher than value (8.5 > 2.660) at level of significance p = 0.05 with degree of freedom (df = 58). It means ha was accepted and ho was successfully rejected. Thus, the analogies strategy significantly affects students’ achievement in vocabulary.